Distinguishing between metastatic and benign adrenal masses in patients with extra-adrenal malignancies - Chen, Jinchao; He, Yedie; Zeng, Xiaowei; Zhu, Shaoxing; Li, Fangyin (Frontiers in Endocrinology, 2022)
Background and Objectives: The adrenal gland is a common organ involved in metastasis. This study aimed to compare adrenal metastases (AMs) and adrenal benign masses (ABMs) of patients with extra-adrenal malignancies during the staging or follow-up. Methods: We retrospectively collected data from 120 patients with AMs and 87 patients with ABMs. The clinical characteristics, imaging features, pathology, and treatment regimes were analysed. Results: The most common types of extra-adrenal malignancies in patients with ABMs included thyroid, kidney, and gynaecological cancers, whereas lung and kidney cancers and lymphoma were the most frequent primary cancers of AMs. The age, male:female ratio, and incidence of symptoms were significantly higher in patients with AM. Radiological analysis showed that AMs tended to have larger tumour sizes and higher attenuation values than ABMs on pre-contrast computed tomography (CT). The diagnostic accuracy of positron emission tomography-CT for AM was 94.1%. An adrenal biopsy had a diagnostic accuracy of 92.5%. A multivariate logistic regression model demonstrated that the origins of extra-adrenal malignancies, the enhancement pattern, and attenuation values in pre-contrast CT were independent predictors of AMs. Conclusions: The differential diagnosis between AMs and ABMs is extremely important, and should be mainly based on imaging and adrenal biopsy results.